2017
DOI: 10.1080/1354750x.2017.1279215
|View full text |Cite
|
Sign up to set email alerts
|

Salivary protein changes in response to acute stress in medical residents performing advanced clinical simulations: a pilot proteomics study

Abstract: Context Quantitative changes of salivary proteins due to acute stress were detected. Objective To explore protein markers of stress in saliva of eight medical residents who performed emergency medicine simulations. Materials and methods Saliva was collected before the simulations, after the simulations, and following morning upon waking. Proteins were separated by SDS-PAGE, identified by MS, and relatively quantified by densitometry. Results Salivary alpha-amylase and S–type cystatins significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
(85 reference statements)
1
4
1
Order By: Relevance
“…Concerning IgA, our findings showed a post task decrease of both the Igα chains isotypes, IGHA1 and IGHA2. This finding contrasts with results of most previous studies, which report an increase of salivary IgA concentration after an acute stress [ 26 , 30 , 31 , 33 , 34 , 35 , 36 , 37 , 38 ]. However, some studies have also highlighted that stress-related IgA secretion is highly influenced by both the experimental protocol and psychological participants’ characteristics.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Concerning IgA, our findings showed a post task decrease of both the Igα chains isotypes, IGHA1 and IGHA2. This finding contrasts with results of most previous studies, which report an increase of salivary IgA concentration after an acute stress [ 26 , 30 , 31 , 33 , 34 , 35 , 36 , 37 , 38 ]. However, some studies have also highlighted that stress-related IgA secretion is highly influenced by both the experimental protocol and psychological participants’ characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…CST2 and CST4 belong to the cystatin superfamily, which prevents cell death caused by virus replication and bacterial invasion by inhibiting cysteine proteases. Our findings are in line with previous studies, which showed an increase of CST2 and CST4 after stress [ 17 , 26 , 38 ] and identified CST4 as a potential marker of acute stress. In the odor group, no change in CST2 and CST4 was found, while a decrease of CSTB occurred.…”
Section: Discussionsupporting
confidence: 93%
“…A high basal salivary cortisol level is predictive of stress resilience [ 9 ] and its use has been suggested to monitor work related stress among occupations at risk such as shift workers. However, the development of knowledge on the pathophysiology of organic stress responses has led to the identification of other biomarkers for the quantitative stress assessment, so higher α-amylase levels can be found in conditions of extreme physical activity, anxiety due to high mental effort and also stress due to sudden changes in the external environment, probably linked to the blood concentration of catecholamine norepinephrine (NE) or epinephrine (E) [ 10 , 11 ]. For this reason, many authors have considered α-amylase as a valid and reliable biomarker of the autonomic nervous system activity.…”
Section: Introductionmentioning
confidence: 99%
“…Salivary amylase along with glutathione S-transferase, and prolactin-induced protein have been shown to correlate with psychosocial stress 4 . In another study, acute stress increased salivary amylase and cystatins in medical students exposed to clinical simulations 5 . Genetically, sAA is coded by AMY1 gene and its copy number is positively correlated with sAA protein expression in humans, and that sAA amount is also positively correlated with its activity 53 , 54 .…”
Section: Discussionmentioning
confidence: 92%
“…Both salivary amylase protein levels and sAA activity have also been used in stress research. Smoking related literature indicates impact on sAA activity as one of the stress related markers 4 , 5 . Given the limited effectiveness of standard of care treatment for nicotine dependence (e.g.…”
Section: Introductionmentioning
confidence: 99%